Witch Stichomythic: from The Confession of Elizabeth Fraunces, late of Hatfeelde in Essex. Issue 3 (December 2020) - Bonnici, Kate Bolton
Abstract : In this piece, Kate Bolton Bonnici deploys a stichomythic technique to create a dramatic dialogue that touches poetically upon the themes of hexing, harboured grievances, retribution, desire, and desire denied. The lines running down the left side of the page, which can be read sequentially on their own, are taken from the pamphlet, A Detection of damnable driftes, practized by three Witches arraigned at Chelmisfforde in Essex, at the Laste Assises there holden, which were executed in Aprill. 1579, which details the confession of Elizabeth Fraunces, a historical figure convicted of witchcraft. Running down the right of the page are lines taken from various sources, which serve to comment, amplify, echo, and counter the details of Fraunces's transgression.